Optimalisasi Pemutakhiran Data Sarana dan Prasarana Dinas Pemadam Kebakaran dan Penyelamatan Kota Samarinda Berbasis Sistem Informasi Geografis sebagai Upaya Pengurangan Risiko Bencana - Muhammad Rizqy Septyandy; Muhammad Amin Syam; Sartika Sartika; Mika Debora Br Barus (Universitas Muhammadiyah Semarang, 2023)
Samarinda is the capital city of East Kalimantan. As the capital city on the second largest island in Indonesia, Samarinda is home to 834,824 residents. A problem that often arises in densely populated cities is fire. In Samarinda, from 2015 to 2022, there have been at least 2,349 fire incidents with a burned area of 8,090,755 m2 so this city has become one of the cities that most often experience fires on Kalimantan. Several supporting facilities and infrastructure owned by the Samarinda Fire and Rescue Agency, such as hydrants and fire posts have been expanded in number. However, most of these supporting facilities have not been integrated with a good coordinate system. So, when a fire occurs, it takes time to identify the location of these vital facilities. As an effort to solve this problem, the Geological Engineering Study Program, Faculty of Engineering, Mulawarman University and Samarinda State Polytechnic of Agriculture held community engagement activities in the form of geographic information system (GIS)-based application training for Samarinda Fire and Rescue Agency officers. This program aims to provide additional competencies needed by field officers in integrating data on facilities and infrastructure such as hydrants and fire posts into the Samarinda geoportal system. Based on the results of this activity, Samarinda Fire and Rescue Agency officers are skilled in operating applications that can integrate coordinate-based facilities and infrastructure data into a geoportal system, including measuring the burned areas accurately and precisely so that fire incidents in Samarinda can be minimized.